Benefits package agreement – a special privilege for employees - Kamosiński, Sławomir (Studia Historiae Oeconomicae, 2015)
The article aims at analyzing a particular occupational privilege of employees, commonly referred to as a benefits package. This social privilege is considered a real social and legal phenomenon by a large number of academics. This is because no legal regulations on the privatization and commercialization of Polish companies actually imposed it. The origin of this specific privilege lies in the pragmatic attitude of employees to the process of privatization of companies and selling their stocks to strategic investors. This type of agreements was supposed to protect staff from radical restructuring which the investor could implement upon buying the company. Owing to this privilege, employees were able to establish their own space of social security in the factory. The article presents examples of such documents, discusses their content and possible sanctions for the new owner of the factory (the signatory of the document) if the provisions of the document are not complied with.